Critical analysis of the limitations of Bleaney's theory of magnetic anisotropy in paramagnetic lanthanide coordination complexes1. Issue 3 (16th March 2015) - Funk, Alexander M.; Finney, Katie-Louise N. A.; Harvey, Peter; Kenwright, Alan M.; Neil, Emily R.; Rogers, Nicola J.; Kanthi Senanayake, P.; Parker, David
<x xml:space="preserve">Abstract</x> The origins of the breakdown of Bleaney's theory of magnetic anisotropy are described, based on an analysis of eleven different complexes of the second half of the 4f elements that form isostructural series.